Respostas

2014-03-13T12:20:20-03:00
2x²+x²+2x-x²-3x+3x-9=2x²+x+x+1

2x²+2x-9=2x²+2x+1


a=2 b=2 c=-9


Δ=2²-4.2.-9
Δ=4-72
Δ=76

√76= 2√19

-b+ou-2√19
       2.2

x¹=-2+2 √19 = √19
         4
x²=-2-2 √19 = -1√19
         4
 

A segunda equação pode ser feita pela soma e produto.

-1+-1=-2
-1.-1=1

2014-03-13T12:25:42-03:00
2X²+x²+2x-(x²-3x+3x-9)=2(X²+x+x+1)
2x²+x²+2x-x²+9=2(x²+2x+1)
2x²+2x+9=2x²+4x+2
2x²-2x²+2x-4x+9-1=0
-2x=-9+1
-2x=-8
x=-8/-2
x=4
correção
essa parte 2x²-2x²+2x-4x+9-2
-2x=-9+2 -2x=-7 x=-7/-2 x=7/2
Ok !